2023
DOI: 10.3389/fimmu.2023.1080391
|View full text |Cite
|
Sign up to set email alerts
|

Myeloidderived suppressor cells: Escorts at the maternal–fetal interface

Abstract: Myeloid-derived suppressor cells (MDSCs) are a novel heterogenous group of immunosuppressive cells derived from myeloid progenitors. Their role is well known in tumors and autoimmune diseases. In recent years, the role and function of MDSCs during reproduction have attracted increasing attention. Improving the understanding of their strong association with recurrent implantation failure, pathological pregnancy, and neonatal health has become a focus area in research. In this review, we focus on the interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 135 publications
0
3
0
Order By: Relevance
“…Presumably, hypoxia, low pH and other tumor microenvironmental factors do not support survival PMN-MDSC [15]. Interestingly, Medical Immunology (Russia)/Meditsinskaya Immunologiya Медицинская Иммунология PMN-MDSC predominates in decidua and blood during pregnancy [9]. In our study, both types of PSG (1 μg/mL nPSG and 10 μg/mL nPSG and rPSG) increased the percentage of M-MDSC in the general MDSC population, and recombinant PSG at a concentration of 10 μg/mL significantly inhibited the formation of PMN-MDSC.…”
Section: Resultsmentioning
confidence: 99%
“…Presumably, hypoxia, low pH and other tumor microenvironmental factors do not support survival PMN-MDSC [15]. Interestingly, Medical Immunology (Russia)/Meditsinskaya Immunologiya Медицинская Иммунология PMN-MDSC predominates in decidua and blood during pregnancy [9]. In our study, both types of PSG (1 μg/mL nPSG and 10 μg/mL nPSG and rPSG) increased the percentage of M-MDSC in the general MDSC population, and recombinant PSG at a concentration of 10 μg/mL significantly inhibited the formation of PMN-MDSC.…”
Section: Resultsmentioning
confidence: 99%
“…MDSCs express the receptor for HLA-G, known as immunoglobulin-like transcript 4 (ILT4). Research has demonstrated that HLA-G can activate STAT3 through ILT4, inducing the production of indoleamine 2,3-dioxygenase (IDO), which in turn promotes immune tolerance to maintain normal pregnancy ( 47 , 48 ). In early pregnancy, elevated levels of estradiol and progesterone in women’s serum activate the ILT4/STAT3 signaling pathway to promote the expansion of MDSCs.…”
Section: The Function Of the Stat Signaling Pathways In Normal Pregnancymentioning
confidence: 99%
“…Immune crosstalk at maternal-fetal interface is considered to play an especially important role for pregnancy maintenance. [122][123][124] However, the quality of oocytes and antioxidants treatment are found equally crucial to determine the developmental potential of embryos, recently. [125][126][127][128] CoQ10 Protects Embryo Development…”
Section: Coq10 and Pregnancy Maintenancementioning
confidence: 99%